Membrane pore formation at protein-lipid interfaces. - Gilbert, R; Dalla Serra, M; Froelich, C; Wallace, M; Anderluh, G (2014)
Pore-forming proteins (PFPs) interact with lipid bilayers to compromise membrane integrity. Many PFPs function by inserting a ring of oligomerized subunits into the bilayer to form a protein-lined hydrophilic channel. However, mounting evidence suggests that PFPs can also generate 'proteolipidic' pores by contributing to the fusion of inner and outer bilayer leaflets to form a toroidal structure. We discuss here toroidal pore formation by peptides including melittin, protegrin, and Alzheimer's Aβ1-41, as well as by PFPs from several evolutionarily unrelated families: the colicin/Bcl-2 grouping including the pro-apoptotic protein Bax, actinoporins derived from sea anemones, and the membrane attack complex-perforin/cholesterol dependent cytolysin (MACPF/CDC) set of proteins. We also explore how the structure and biological role of toroidal pores might be investigated further.